Synthesis, in vitro and in silico studies of a novel chrysin-ferrocene Schiff base with potent anticancer activity via G1 arrest, caspase-dependent apoptosis and inhibition of topoisomerase II - Mohammed Khaled Bin Break; Siddique Akber Ansari; Ahmed A. Katamesh; Najah Albadari; Maali D. Alshammari; Hamad M. Alkahtani (Journal of Enzyme Inhibition and Medicinal Chemistry)
A novel chrysin-ferrocene Schiff base (CFSB) was synthesised as a potential anticancer agent. CFSB demonstrated high cytotoxicity against cancer cells with HepG2 (liver) being the most susceptible (IC50 = 3.11 µM). The compound was less toxic towards normal MRC5 cells and exhibited ∼5-fold selectivity towards most cancer cells. CFSB caused G1-phase arrest, induced caspase-dependent apoptosis by increasing Bax/Bcl2 ratio and reduced metastasis by decreasing MMP9 in HepG2. Furthermore, CFSB was inactive against CDK2, EGFR, TrkA and VEGFR, but it strongly inhibited topoisomerase II (IC50 = 20 µM) with potency comparable to etoposide (IC50 = 15 µM), while weak inhibition was observed against tubulin (IC50 = 76 µM). DFT calculations revealed that CFSB had desirable reactivity, while docking indicated high binding affinity with topoisomerase II. Molecular dynamics and MM-GBSA analyses showed that CFSB-topoisomerase II complex was stable with favourable binding energies, while in silico ADMET studies showed drug-like properties for CFSB.